Porous g-C3N4 with defects for the efficient dye photodegradation under visible light - Jing Chen (IWA Publishing, 2021)
Porous graphitic carbon nitride (p-C3N4) was fabricated via simple pyrolyzing treatment of graphitic carbon nitride (g-C3N4). The defects could be introduced into the structure of g-C3N4 by breakage of some bonds, which was beneficial for the generation of electron–hole pairs and inhibiting their recombination. Compared with g-C3N4, p-C3N4 showed a narrow band gap to promote the utilization of visible light. Furthermore, the porous structure also increased the specific surface area to maximize the exposure of active sites and promote mass transfer during photodegradation. As a result, the as-reported p-C3N4 exhibited considerably higher degradation efficiency for Rhodamine B (RhB) and Methyl Orange (MO) than that of the original g-C3N4. Moreover, the photocatalyst showed high durability and stability in recycling experiments. HIGHLIGHTS Facile synthesis process for the porous catalyst.; Metal-free components.; The band gap of the catalyst is 2.59 eV in visible light region.; The defects can inhibit the recombination of electrons and holes.; Excellent photocatalytic degradation efficiency and high stability for industrial dyes.;